Método automático para determinação fotométrica direta de Fe (III) em amostras de óleos comestíveis - Nóbrega, Maria Daisy Oliveira da (2013)
In this study a flow-batch analyzer (FBA) was utilized and its performance was evaluated for the determination of Fe(III) in edible without external pretreatment. The FBA method uses the reaction between Fe(III) and thiocyanate in organic medium. The formed red complex was monitored by employing a light emitting diode (LED, λmax = 520 nm) and a phototransistor linked to the mixing chamber by optical fibers. All standard solutions were prepared in-line and all analytical processes were carried out by simply changing the operational parameters in FBA control software. Comparing with the reference method, no statistically significant differences were observed when applying the paired t-test at a 95% confidence level. For the three types of samples studied the estimated standard deviation was less than 0.03 mg kg-1 (n = 3). The analytical frequency was 95 h-1, the limit of detection was 0.004 mg kg-1 and the limit of quantification was 0.013 mg kg-1. The recovery study shows results between 98.4% and 104.2%. The FBA method showed better analytical features when compared with previous automatic flow methods. Thus, the automated method proposed is potentially useful as an alternative for the determination of other ions in similar samples or in other viscous matrices without external pretreatment.